POLITICAL EDUCATION TO INCREASE POLITICAL PARTICIPATION THROUGH POLITICAL PARTIES - Zainul Djumadin (Jurnal Scientia, 2023)
Political education is considered an effective means of providing a better understanding of the political system, the rights and responsibilities of citizens, as well as the importance of active participation in the political process. This research aims to analyze the impact of implementing political education on increasing community political participation through political parties. This research method involves literature studies, surveys, and qualitative data analysis. The research results conclude that political education through political parties has a significant role in shaping community political participation. The concept of political education includes increasing citizens' knowledge and awareness of political issues, political rights, and their role in the political process. Political parties, as the main agents of political education, are responsible for conveying clear information about their political platforms and encouraging active participation of citizens in general elections. Political education also plays a crucial role in equipping society with political skills and an understanding of the complexities of public policy. Through this effort, it is hoped that people can become intelligent, critical and responsible voters, and be actively involved in building a sustainable democratic country.